Intussusception, A Rare Presentation of MIS-C.: Life Sciences-Pediatric Medicine and surgery - S, Jayakanthan; A.P, Krithika (International Journal of Life Science and Pharma Research, 2022)
Intussusception refers to the invagination of one part of intestine into itself. It is the most common abdominal emergency encountered in children younger than 2 years of age. Multisystem inflammatory syndrome in children or pediatric inflammatory multisystem syndrome temporally associated with covid -19PIMS-TS is a relatively rare complication of COVID 19 infection occurring in<1% of children who may have a past history of confirmed covid-19 infection. Many cases of intussusception are reported when a child suffers from acute covid 19 infection. But a case of intussusception which itself is a manifestation of MIS-C is not reported so far. A 7-year-old boy presented with fever, abdomen pain was found to have ileocolic intussusception. It was then successfully reduced pneumatically. But he continued to have high temperatures and later developed mucocutaneous manifestations and shock. Keeping the current pandemic in view, he was investigated and was found to be suffering from MIS-C. He was then treated by our hospital protocol successfully. This is a rare presentation of MIS-C, and so is reported here. This 7year old boy presented with fever, abdomen pain and was found to have ileocolic intussusception. It was then reduced pneumatically. He continued to have high temperature and later developed mucocutaneous manifestations and shock. With the investigations, he was found to be suffering from MIS-C. He was then treated by our hospital MISC-C protocol successfully. This is a rare presentation of MIS-C, which warrants a high index of suspicion.